QSAR STUDY OF FLAVONE / FLAVONOL ANALOGUES AS THE ANTIRADICAL COMPOUNDS BASED ON HANSCH ANALYSIS - Iqmal Tahir; Karna Wijaya; Bambang Purwono; Dinni Widianingsih (Indonesian Journal of Chemistry, 2003)
Quantitative Structure-Activity Relationship (QSAR) analysis of substituted flavone / flavonol compounds has been carried out by applying Hansch Analysis using their physicochemical properties as the predictors. The properties i.e. log P, (log P)2, core-core interaction energy (Eint), volume (V), molecular mass (M), dipole moment (μ), heat of formation (ΔHof), binding energy (Ei), total energy (ET), surface area (L), polarizability (α), molar refractivity (RM), hidration energy (EH), electronic energy (Eel) and isolated atomic energy (Eat,is), were obtained on the basis of geometry optimization using PM3 semiempirical method. The QSAR analysis used antiradical activities (% A) as the dependent variable and has been done by applying multilinear regression technique. The result showed that QSAR equations i.e.% A  =  77.426 - 67.343  [log P] + 3.160 [(log P)2 + 67.884 [α] + 6.63x10-4 [ Eint] - 5.280 [L] + 1.179 [V] + 0.447 [M] - 11.000 [μ]  + 0.093 [Ei]  + 3.433 [EH] - 3.44x10-3 [ET](n = 16 ; r2 = 0.987 ; SD = 9.205; Fcal/Ftable = 4.797)